2006
DOI: 10.1016/j.triboint.2006.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on mechanical properties of zinc dithiophosphate tribofilms

Abstract: Nanoindentation tests were performed at several temperatures (24 to 80°C) on one antiwear zinc dialkyl-dithiophosphate (ZDTP) tribofilm using a Nanoindenter XP ® entirely set into a climatic chamber. Mechanical properties of the tribofilm were determined using a simple model. AFM observations were conducted to estimate the order of magnitude of the film's thickness. The effect of applied pressure on the elastic properties was demonstrated and taken into account in the present analysis. The use of the ( ) 2 F S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 20 publications
(24 reference statements)
1
42
0
3
Order By: Relevance
“…Due to the lower hardness and higher plastic flow, more indentation occurs into the depth of the tribofilm and more tribofilm thickness reduction is observed. Results are in agreement with the previous study of the temperature effects on the mechanical properties of ZDDP [21,55].…”
Section: Effect Of Temperaturesupporting
confidence: 93%
See 1 more Smart Citation
“…Due to the lower hardness and higher plastic flow, more indentation occurs into the depth of the tribofilm and more tribofilm thickness reduction is observed. Results are in agreement with the previous study of the temperature effects on the mechanical properties of ZDDP [21,55].…”
Section: Effect Of Temperaturesupporting
confidence: 93%
“…These have demonstrated that the properties of the ZDDP tribofilm layers are dependent on applied load [20,21].…”
Section: Mechanical Properties and Durability Of Zddp Tribofilmmentioning
confidence: 97%
“…The hardness at the surface is lower than the bulk hardness; as the penetration depth increases the hardness increases linearly [48,49].…”
Section: Tribofilm Propertiesmentioning
confidence: 96%
“…The effect of the steel substrate in changing the nano-indentation results of tribofilm has been reported and different models for extracting the tribofilm properties were developed [7,48]. In this work the results reported for the mechanical properties of tribofilm based on those models has been used.…”
Section: Tribofilm Propertiesmentioning
confidence: 99%
See 1 more Smart Citation